PENGARUH KONSELING KELOMPOK TERHADAP PENURUNAN MASALAH HUBUNGAN SOSIAL SISWA KELAS X IPS SMA NEGERI 5 PEKANBARU TAHUN AJARAN 2014/2015 - Nurwinda Sari Nurwinda Sari; Elni Yakub Elni Yakub; Rosmawati Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims 1) To know the description of social relationship problems experienced by students before given group counseling. 2) To know the description of social relationship problems experienced by students after the given group counseling. 3) To know how the process of implementation of group counseling in reducing social relationship problems experienced by students. 4) To determine differences in social relationship problems experienced by students before and after group counseling. 5) To determine how much influence the group counseling on reducing social relationship problems experienced by students. Data collection tool in the form of scale of the problem of social relationships. The subjects were students of class ten grade social students of State Senior High School 5 Pekanbaru a total of 11 people. The samples using purposive sampling technique, meaning that the sample is a sample taken in accordance with criteria established by the researcher. Overview of social relationship problems experienced by students before given group counseling services are in many categories, namely 100%. Overview of social relationship problems experienced by students after a given group counseling services are decreasing in many categories of 0%, at katgori was 18%, in the category of less than 73%, and least 9%. Based on the calculation of correlation coefficient between and is determinant of 0.44 and a coefficient of = 0.19 it means donation group counseling services to the decline of social relationship problems experienced by students by 19%. It can be seen greater than (16.41> 2.086) so that Ha is accepted. Means that there are significant group counseling services to the decline of social relationship problems experienced by students of class ten grade social students of State Senior High School 5 Pekanbaru Academic Year 2014/2015.Keywords: Group Counseling Services, Social Relationship Problems